2014
DOI: 10.3856/vol42-issue4-fulltext-2
|View full text |Cite
|
Sign up to set email alerts
|

Ancient fishing activities developed in Easter Island

Abstract: Easter Island, Rapa Nui or Te pito o te henua, is in the middle of the Pacific Ocean halfway between South America and Oceania, constituting one of the most isolated places on the planet. It was colonized by Polynesians at the end of the first millennium of the Christian era, thus becoming one of the extremes of the Polynesian triangle. The island is of volcanic origin, has a small surface area (166 km 2 ) and limited resources, and gave rise to a culture that is unique in the world, recognized internationally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Nonetheless, the numbers of fish hooks found in caves and archeological excavations, the abundant representation of marine animals in petroglyphs and the frequent inclusion of sea-related themes in the island's folklore suggest the use of fish protein from ancient times. In fact, the islanders identified distinct fishing zones (Arana, 2014). The tactics and methods used bear close relation to the systems of other Polynesian islands, demonstrating notable adaptation to the resources available on this island.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Nonetheless, the numbers of fish hooks found in caves and archeological excavations, the abundant representation of marine animals in petroglyphs and the frequent inclusion of sea-related themes in the island's folklore suggest the use of fish protein from ancient times. In fact, the islanders identified distinct fishing zones (Arana, 2014). The tactics and methods used bear close relation to the systems of other Polynesian islands, demonstrating notable adaptation to the resources available on this island.…”
mentioning
confidence: 75%
“…However, 669 Advances in oceanographic, ecological and fisheries research on Oceanic Islands 5 we know very little on the important and increasing human effects on coastal marine communities in ocean islands, such as fishing. Arana (2014) nicely describes ancient fishing boats and gears, though it is difficult to establish a concrete idea of the real importance of fishing on this island before the arrival of Europeans. Nonetheless, the numbers of fish hooks found in caves and archeological excavations, the abundant representation of marine animals in petroglyphs and the frequent inclusion of sea-related themes in the island's folklore suggest the use of fish protein from ancient times.…”
mentioning
confidence: 99%
“…The official Management Plan for Rapa Nui National Park was drafted in 1997 (CONAF, 1997). So far, comprehensive reviews about the natural history and fisheries of Easter Island have been published by Echeverría & Arana (1978), Castilla (1987) and Arana (2014).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of bone and stone fishhooks also attest to the creation of tools specifically for acquiring fish (M etraux, 1940). In addition, it has been suggested that microwear patterns on prehistoric human dental enamel are consistent with seafood consumption (Polet, 2011) and petroglyphs could suggest the cultural importance of fishing (Arana, 2014). However, estimates of the relative contribution of seafood to Rapa Nui diets vary considerably;…”
Section: Introductionmentioning
confidence: 99%
“…The presence of bone and stone fishhooks also attest to the creation of tools specifically for acquiring fish (M etraux, 1940). In addition, it has been suggested that microwear patterns on prehistoric human dental enamel are consistent with seafood consumption (Polet, 2011) and petroglyphs could suggest the cultural importance of fishing (Arana, 2014 Marticorena, Rojas, & Barrera, 2015). This is of particular relevance in isotopic studies as most invasive grasses on Rapa Nui are C 4 plants in the subfamilies Chloridoideae and Panicoidae, which make up 60% of the grass species, whereas indigenous grasses were dominantly C 3 plants (Finot et al, 2015).…”
mentioning
confidence: 99%